Pengaruh Budaya Organisasi, Kepuasan Kerja, dan Gaya Kepemimpinan Terhadap Komitmen Organisasi PT BCA Tbk. KCU Bekasi - Shilastio; Asrul; Andi Muhammad Sadli (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
The writing of this thesis is the result of a survey at PT BCA, Tbk. KCU Bekasi by discussing how far the influence of organizational culture, job satisfaction and leadership style on organizational commitment. PT BCA. Tbk, KCU Bekasi has 122 workers with various cultural, educational and age backgrounds. With a relatively large number of employees, of course there are various kinds of conflicts which eventually make workers leave the company or in other words have low organizational commitment. Based on the above, the problem to be discussed in writing this thesis is entitled “The Influence of Organizational Culture, Job Satisfaction and Leadership Style on PT BCA's Organizational Commitment. Tbk, Bekasi Branch Office.